The impact of corporate social responsibility on the risk of commercial banks with different levels of financial constraint. Issue 1 (8th December 2020) - Nguyen, Liem Thanh; Nguyen, Khuong Vinh
Abstract : Purpose: This research investigates the link between corporate social responsibility (CSR) activities and bank risk-taking in Vietnam and introduces the constraint factor to see whether this link alters with different levels of constraint. Design/methodology/approach: Using a sample of commercial banks in Vietnam from 2008 to 2017, this study employs two-step system generalized method of moments (Sys GMM) with a finite sample correction mechanism to estimate the models. Findings: The results suggest that CSR activities reduce bank risk-taking, and this relationship is only present in the case of financially constrained banks. Unconstrained banks, on the other hand, are more likely to invest in unnecessary CSR, thus reducing bank performance and increasing bank risk-taking. Research limitations/implications: The first implication from this study is that CSR activities might be considered as a risk-mitigating tool and should be invested in that respect. Secondly, regulatory units and investors should be more cautious about CSR expenditures since this type of spending could increase default risk, especially for banks with easy access to external financing. One particular limitation of this study is the low number of observations available for banks in Vietnam. Future studies could use texture analysis to expand the sample or consider macro-level governance characteristics to examine which factors might modify the relationship between CSR and bank risk. Originality/value: Very limited studies discussed the link between corporate social responsibility and bank performance and bank risk. There are even fewer papers examining the relationship between CSR and risk, and most of these papers deal with advanced economies. Furthermore, no studies investigate the interaction effect of CSR and financial constraint, which should be prevalent in developing countries on bank risk. As a consequence, the current study seeks to verify the impact of financial constraints on the link between CSR and bank risk.